The Sundanese Puppets Appearance as The Representation of Their Characters in Mahabharata Play - Lisdawati, Ida (LPPM Universitas Advent Indonesia, 2017)
This study not only aims to introduce Sundanese culture which is part of Indonesian culture, but also analyses the phenomenon that exists in Sundanese puppets performance as one of the entertainment for the Sundanese people with Semiotic. In this study, the researcher analyzed two factors that determined the result of this research. Firstly, the researcher found the role of color as a kind of pictorial metaphor. In each puppet, it will be seen whether the dominant color of puppet represents the characteristics corresponding to the color or has a significant difference. The secondly, the researcher analysed the appearance of each puppets. This research used four puppets from category of Panakawan, two puppets from category of Knight, and two puppets from category of Giant. Qualitative method is used for describing the result and the result showed that almost puppets appearance represented their character except Cepot that also known as Astrajingga. His appearance did not represent his characteristic especially his color face.Keyword: Semiotics, Sundanese puppets, color of Sundanese puppet